Dynamics between toroidal Alfvén eigenmode evolution and turbulence suppression under resonant magnetic perturbations on EAST. (13th July 2021) - Li, P.; Li, Y.D.; Li, J.G.; Wu, G.J.; Chen, W.; Geng, J.S.; Chen, F.; Wang, Y.H.; Zhang, B.; Xu, L.Q.; Sun, P.J.; Li, E.Z.; et al.
Abstract: Since Alfvén activity and turbulence are ubiquitous in magnetically confined plasma, it is important to understand the possible roles Alfvén activity have in the nonlinear evolution of turbulence. The designed experiments in low collisionality are dedicated to studying the dynamics between turbulence and toroidal Alfvén eigenmodes (TAEs), and assessing the multi-scale physics on the long-term scale behavior of fusion plasma. In TAEs ( f ∼ 200 kHz, n = 1) mitigation experiments under resonant magnetic perturbations (RMP, n upper = 2 and n lower = 3), there is a long-term (∼500 ms) quasi-stationary state after RMP rapidly reduces the TAEs amplitude four times. Turbulence suppression (2.0 < kρ s < 3.8) and low-frequency zonal flow (LFZF) generation are observed in this period. Similar experiments show that energetic particles (EPs) may act as a mediator of the cross-scale interactions and are beneficial for turbulence suppression and LFZF generation. Besides the synchronous couplings of turbulence (2.0 < kρ s < 3.8) and TAEs, TAEs and LFZF are observed. The dynamics between turbulence and TAEs provides an idea for synchronous control of TAEs and turbulence, and the resulting EPs confinement improvement, T e increase, T i increase and plasma stored energy increase are favorable for plasma performance.